Conceptual and Legal Framework for Promotion of Education for Sustainable Development: Case Study for Ukraine - Hudima , Tetiana; Malolitneva, Vesta (European Journal of Sustainable Development, 2020)
Promoting the sustainable development is currently a key global issue posing a challenge to all of us on personal, professional and political levels. The education plays a major role in this path, in particular the education for sustainable development (ESD). The traditional one-way transfer of knowledge is no longer sufficient to inspire the students to behave as responsible citizens. This article suggests a number of competencies, which must serve as a basis for ESD, as well as application of the multiple intelligence theory as a mechanism for implementing the competencies derived by students from ESD at the basic education level. It is proved that security competencies in the broadest sense (covering all levels, from personal to the global space) should also be included in the modern educational process. As for the university education, it is required to explain the concept of "sustainability" to all specialties without exception, including the political scientists, engineers and others. This is particularly important for training of experts dealing with the economic law issues. A lack of economic analysis in modern legal studies and development of regulations results in writing and adoption of idle laws hazardous for the country. To upgrade the education system in Ukraine, it is appropriate to develop the National Strategy on Education for Sustainable Development and its implementation plan based on the global Sustainable Development Goals. It is required to switch from traditional education to the model focused on sustainable development with the underlying extensive interdisciplinary knowledge based on an integrated approach to the development of society, economy, and environment. Implementation of this strategy should consider the adaptive nature of the regional education component, in particular the economic features of a relevant region. It is important to focus on the learning processes underlying the circular economy. Keywords: sustainable development, society, economy, environment, circular economy, education for sustainable development, sustainability, economic law.